Music for Hope: Transforming Social Reality in a Vulnerable Neighborhood of Costa Rica - Zamora Ulate, Mauricio (2025)
Community music practice differs from traditional conservatory learning in that students are not required to work for a grade. Instead, they are motivated by a shared group goal, such as a concert performance, in which the collective image of the group is presented by all its members. This study explores the experience of participating in community music practice through the perspectives and lived experiences of the young participants of the National System of Music Education in León XIII, San José, Costa Rica. A qualitative methodology with an autoethnographic approach was employed, aiming to understand the processes involved in interpreting personal narratives. Based on the analysis of the data obtained from interviews with students, teachers, and family members participating in the program, it was possible to highlight how community music positively impacts the quality of life of participants, as it facilitates the technical knowledge of playing an instrument and enhances the ability to manage and understand their own emotions as well as those of others. It is concluded that these skills are essential for promoting social, political, and economic development in communities affected by high levels of inequality and poverty.